2015
DOI: 10.4212/cjhp.v68i2.1439
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for and Outcomes of Bacteremia Caused by Extended-Spectrum ß-Lactamase– Producing Escherichia coli and Klebsiella Species at a Canadian Tertiary Care Hospital

Abstract: Background: Antimicrobial resistance due to production of extendedspectrum ß-lactamases by Escherichia coli and Klebsiella species (ESBL-EK) is concerning. Previous studies have shown that bacteremia due to ESBLproducing organisms is associated with increases in length of stay and/or mortality rate. Rates of infection by ESBL-EK vary worldwide, and regional differences in the prevalence of risk factors are likely. Few Canadian studies assessing risk factors for ESBL-EK infections or the outcomes of empiric the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
(39 reference statements)
5
9
1
Order By: Relevance
“…Our study also demonstrated a significant association between previous antibiotic use and CTXNS-En bacteremia in the univariate analysis. Prior isolation of CTXNS-En also appears to be a potent risk factor [4, 6, 24], as shown in our study. These common risk factors found in both previous studies and our study may help to identify patients with CTXNS-En bacteremia.…”
Section: Discussionsupporting
confidence: 76%
“…Our study also demonstrated a significant association between previous antibiotic use and CTXNS-En bacteremia in the univariate analysis. Prior isolation of CTXNS-En also appears to be a potent risk factor [4, 6, 24], as shown in our study. These common risk factors found in both previous studies and our study may help to identify patients with CTXNS-En bacteremia.…”
Section: Discussionsupporting
confidence: 76%
“…Strikingly, a 4-fold difference in the number of carriers compared to noncarriers acquiring HAP due to K. pneumoniae was observed following a hospital stay of more than 3 weeks (127). As previously noted, antibiotic treatment amplifies the risk of K. pneumoniae infection, and recent antibiotic use is an additional independent risk factor for colonization by and infections with ESBL-and carbapenemase-producing K. pneumoniae (128)(129)(130)(131).…”
Section: Patient Risk Factorsmentioning
confidence: 55%
“…Full-text screening excluded an additional 5 articles, providing an evidence base of 87 studies (figure 1). 10–96 The 87 studies included in the qualitative analysis were conducted between 1991 and 2017 in 25 countries, mainly in South Korea (14 studies), Thailand (7), USA (7), Taiwan (7) and Spain (7). Sixty (68.9%) studies were performed in HICs, 26 (29.9%) in LMICs and 1 included both HICs and LMICs 56.…”
Section: Resultsmentioning
confidence: 99%